Implementation of Child Rights Protection Against Economic Exploitation in Pekanbaru City Based on Pekanbaru City Regulation Number 2 of 2023 concerning the Protection of Women and Children - Salsabilla Risti Ananda; Eddy Asnawi; Silm Oktapani (CV. Akira Java Bulu, 2025)
Based on Article 11 Letter d of Pekanbaru City Regulation No. 2 of 2023 concerning the Protection of Women and Children (Perda No. 2/2023), it is stipulated that every child has the right to protection from economic exploitation. From the research observations conducted in the City of Pekanbaru, the researcher directly observed children working as newspaper vendors, street performers, tissue sellers, car window cleaners, and some were employed as silver men and clowns. The method used in this research is sociological legal research. The research findings indicate that the implementation of child rights protection against economic exploitation in the city of Pekanbaru based on Local Regulation No. 2/2023 has not been optimal. The obstacles in the implementation of child rights protection against economic exploitation in Pekanbaru City based on Local Regulation No. 2/2023 include insufficient supervision by the Department of Women's Empowerment, Child Protection, and Community Development of Pekanbaru City, as well as budget constraints for operational funds at the Department of Women's Empowerment, Child Protection, and Community Development of Pekanbaru City, the Social Affairs Department of Pekanbaru City, and the Pekanbaru City Public Order Agency (SATPOL PP). Efforts made based on Local Regulation No. 2/2023 include the Department of Women's Empowerment, Child Protection, and Community Development of Pekanbaru City enhancing its supervision and coordinating and collaborating across agencies with the Social Affairs Department of Pekanbaru City and the Pekanbaru City Police Department by scheduling routine patrols at several traffic light locations in Pekanbaru City. The recommendation is that the Department of Women's Empowerment, Child Protection, and Community Empowerment of Pekanbaru City, the Social Affairs Department of Pekanbaru City, and the Pekanbaru City Police should provide protection for children by conducting routine patrols and enforcement at several traffic light locations in Pekanbaru City to regulate children who are exploited, as Pekanbaru City is a Child-Friendly City. The Department of Women's Empowerment, Child Protection, and Community Development of Pekanbaru City should coordinate with the Women and Children's Service Unit of the Pekanbaru City Police Department (Polresta) to address cases of child exploitation or parents suspected of economically exploiting their children.